Embedded Radiation sensor with OBIST structure for applications in mixed signal systems - Pablo Petrashin; Walter Lancioni; Agustín Laprovitta; Juan Castagnola (Department of Electrical Engineering ITS and FORTEI, 2021)
Oscillation based testing (OBT) has proven to be a simple and effective test strategy for numerous kind of circuits. In this work, OBT is applied to a radiation sensor to be used as a VLSI cell in embedded applications, implementing an oscillation built-in self-test (OBIST) structure. The oscillation condition is achieved by means of a minimally intrusive switched feedback loop and the response evaluation circuit can be included in a very simple way, minimizing the hardware overhead. The fault simulation indicates a fault coverage of 100% for the circuit under test.Keywords: fault simulation, mixed signal testing, OBIST, oscillation-based test, VLSI testing.